Development of Potato-Boro-T. Aman Rice Cropping Pattern Against Fallow-Boro-T. Aman Rice Cropping Pattern at Mymensingh (Bangladesh Journal of Agricultural Research, 2022)
The experiment was conducted at Multiplication Testing Site (MLT) Trishal of On-Farm Research Division, Bangladesh Agricultural Research Institute, Mymensingh during 2017-18 and 2018-19 to evaluate the agro-economic performance of improved cropping pattern for increasing cropping intensity and system productivity as compared to farmers’ existing cropping pattern. The experiment was laid out in randomized complete block design with six dispersed replications. Two cropping patterns viz. improved pattern Potato (BARI Alu- 25)-Boro (BRRI dhan28)-T. Aman rice (BRRI dhan49) and farmers existing cropping pattern Fallow-Boro (BRRI dhan29)- T. Aman rice (BRRI dhan49) were treatments variables of the experiment. Two years mean data showed that Potato-Boro-T. Aman rice cropping pattern produced higher tuber/grain yield as well as higher rice equivalent yield (30.53 t ha-1yr-1), production efficiency (149 kg ha-1 day-1), land utilization index (74 %) and labour employment (367mandays ha-1 yr-1) than Fallow-Boro-T. Aman rice cropping pattern. This pattern also increased system productivity, production efficiency, land utilization index and labour employment by 158, 166, 26 and 51% higher over exiting pattern. The mean gross return (Tk. 481800 ha-1) and gross margin (Tk.235329 ha-1) of improved cropping pattern were 139 and 237% higher, respectively compared to existing pattern with 87% extra cost. The mean marginal benefit cost ratio (2.45) indicated superiority to improved cropping pattern over existing pattern. Experimental findings revealed that there is potential for greater adoption of intensified cropping systems with increased productivity and profitability as compared to rice–rice systems in Mymensingh.Bangladesh J. Agril. Res. 45(3): 279-292, September 2020